Auditory P300 event related potentials and serotonin reuptake inhibitor treatment in patients with fibromyalgia - Ozgocmen, S; Yoldas, T; Kamanli, A; Yildizhan, H; Yigiter, R; Ardicoglu, O (British Med Journal Publ Group, 2003)
Background: The P300 components of auditory event related potentials (ERPs) are objective measures related to information and cognitive processing. Objectives: To assess P300 ERPs in female patients with fibromyalgia (FM) in comparison with healthy age matched controls. To investigate the relationship between P300 potentials and pain threshold levels of patients, and subsequent effect of sertraline treatment on P300 potentials. Methods: P300 auditory ERPs were studied in 13 untreated female patients with FM and 10 healthy controls matched for age, sex, and education. Pain pressure thresholds and total myalgic scores (TMS) were assessed with an algometer. Patients were evaluated for clinical measures and P300 potentials (recorded from the vertex) at the first visit, and then in the fourth and eighth weeks of sertraline treatment. Results: Patients with FM had significantly lower P300 amplitudes, but not significantly different P300 latencies, than controls at entry. P300 latencies in patients correlated negatively with TMS (r(s) = -0.79, p<0.01) and P300 amplitudes correlated significantly with TMS (r(s) = 0.53, p<0.05). Anxiety and depression scores did not correlate significantly with P300 latencies or amplitudes at the study entry. P300 auditory ERPs had increased amplitudes that had reached nearly the same levels as those of the controls at the eighth week without any significant change in their latencies. Conclusion: The results show reduced P300 amplitudes in patients with FM. Further studies assessing the relationship between P300 ERPs and neuropsychiatric tests are required for better clarification of the clinical relevance of P300 potentials in FM.
Keywords: Major Depression; Healthy Controls; Reliability; Disorder; Brain; Erp